Development and clinical validation of the Genedrive point-of-care test for qualitative detection of hepatitis C virus - Llibre, Alba; Shimakawa, Yusuke; Mottez, Estelle; Ainsworth, Shaun; Buivan, Tan-Phuc; Firth, Rick; Harrison, Elliott; Rosenberg, Arielle R.; Meritet, Jean-Francois; Fontanet, Arnaud; Castan, Pablo; Madejon, Antonio; et al. (BMJ Publishing Group, 2018)
Objective: Recently approved direct acting antivirals provide transformative therapies for chronic hepatitis C virus (HCV) infection. The major clinical challenge remains to identify the undiagnosed patients worldwide, many of whom live in low-income and middle-income countries, where access to nucleic acid testing remains limited. The aim of this study was to develop and validate a point-of-care (PoC) assay for the qualitative detection of HCV RNA.